Optimization of Pectin-Zein Beads via Response Surface Methodology for Enhanced Colon-Targeted Delivery of p-Coumaric Acid from Rice Husk Extract - Ilaria Frosi; Raffaella Colombo; Chiara Milanese; Adele Papetti (Foods)
The generally very low bioaccessibility of polyphenols can be enhanced through several different strategies, especially when these metabolites are components of extracts used as food ingredients. This work explores the efficacy of pectin-zein beads as carriers for delivering p-coumaric acid), the main component of rice husk extract. Ten formulations were prepared using the ionic gelation technique, employing a Taghuci Design of Experiments to optimize zein, pectin, and CaCl2 concentrations. Zein content was found as the main parameter affecting the encapsulation efficiency. The highest value (51.77 ± 1.13%) was achieved using 10% zein, 3% pectin, and 4% CaCl2. p-coumaric acid bioaccessibility in the raw and encapsulated extracts was evaluated by adopting the Infogest digestion protocol and simulating a colon phase with Pectinex® Ultra SPL enzymes, evidencing that pectin-zein beads effectively improved p-coumaric acid stability in the extract. The encapsulation highly preserves p-coumaric acid during the gastric phase (bioaccessibility index 34%); conversely, an increased release was registered at the intestinal level, reaching approximately 80% and 100% during the duodenal and colon steps, respectively. Therefore, pectin-zein beads were demonstrated to be a promising tool for the development of active ingredients suitable for functional foods/food supplements aimed at enhancing health benefits through controlled intestinal delivery of bioactives.